Creating a qualified cannabis workforce: how higher education can support cannabis career pathways - Black, Becky E. (Kansas State University, 2020)
Background The popularity of medicinal and recreational cannabis is increasing the need for a trained workforce. The purpose of this study is to examine the workforce needs of the cannabis industry from the perspective of cannabis industry experts. The findings will assist institutions that are providing or plan to offer cannabis academic courses and programs. To meet and respond to the dynamic evolution of the cannabis industry, colleges will need to be nimble or find ways to be nimble. Methods This qualitative study utilized Heidegger's interpretative phenomenological research design to capture the essence of eight cannabis industry professionals’ (three females, five males) experience and interpretation of the workforce needs of the growing cannabis industry. Purposive sampling and snowball sampling determined the subjects for the remotely recorded, unstructured, six-question, in-depth interviews. The interviews ranged in length from 49 minutes to 126 minutes. The researcher transcribed the interviews verbatim, then coded and analyzed results for themes and implications for practice. The purpose of this methodology is to describe the essence of the research subjects’ lived experiences. The researcher did not bracket their biases. Results Research subjects had from two months to 12 years of experience working in the legal cannabis industry; from three years being affiliated with the cannabis industry and up to 43 years being in the black or black and gray market. They held cannabis licenses in cultivation, manufacturing, distribution, and/or retail. Education ranged from post-secondary to master’s degree. All of the research subjects self-identified as being White, non-Hispanic, and ages ranged from 30 to 59. Coding methods included in vivo coding, eclectic coding, focused coding and a top-10 list was used to transition between post-coding and prewriting. Abridged interviews yielded seven themes for higher education. The phenomenological essence of the interviewees lived experience was love and passion for the cannabis plant, growing it as well as its medicinal properties. Conclusion Academia has the opportunity to support cannabis career pathways by providing cannabis classes and/or programs, thus helping to create a qualified cannabis workforce. The research findings within this study can assist in the design and implementation of these programs.
Keywords: Cannabis industry workforce needs; Cannabis industry experts; Love and passion for cannabis; Endocannabinoid system; Cannabis; Cannabis higher education academic courses; THC; CBD